2020
DOI: 10.1073/pnas.2007201117
|View full text |Cite
|
Sign up to set email alerts
|

Supertertiary protein structure affects an allosteric network

Abstract: The notion that protein function is allosterically regulated by structural or dynamic changes in proteins has been extensively investigated in several protein domains in isolation. In particular, PDZ domains have represented a paradigm for these studies, despite providing conflicting results. Furthermore, it is still unknown how the association between protein domains in supramodules, consitituting so-called supertertiary structures, affects allosteric networks. Here, we experimentally mapped the allosteric ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…7 ), which is required for inhibition of phosphate transport ( 16 ). Allosteric networks and allosteric communication are essential regulators of PDZ-containing multidomain protein conformational changes and function ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…7 ), which is required for inhibition of phosphate transport ( 16 ). Allosteric networks and allosteric communication are essential regulators of PDZ-containing multidomain protein conformational changes and function ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inter-domain energetic communication within the PSG supramodule was also investigated by double mutant cycles [ 58 ]. The so-called ‘double mutant cycles’ methodology is a powerful approach to measuring, directly, the extent of energetic communication between interacting side-chains.…”
Section: Interaction Between Protein Domains—supertertiary Structurementioning
confidence: 99%
“…In this context, double mutant cycles proved very useful. An extensive double mutant cycle analysis of a PDZ domain, both in isolation and in the context of a supramodule comprising the PDZ domain, an SH3 and a GK domain, showed that allosteric networks are highly sensitive to the supertertiary structure [ 45 ]. In particular, it was found that the presence of the SH3–GK tandem resulted in strong coupling from the bound peptide ligand to the β1β2 loop, β2β3 loop, and α3 helix that was not observed with the single PDZ3 domain.…”
Section: Protein Binding and Allosterymentioning
confidence: 99%